On the road - Kerouac , Jack (London : Penguin Books, 1955)
Follows the counterculture escapades of members of the Beat generation as they seek pleasure and meaning while traveling coast to coast. As he travels across 1950s America, aspiring writer Sal Paradise chronicles his escapades with the charismatic Dean Moriarty. Sal admires Dean's passion for experiencing as much as possible of life and his wild flights of poetic fancy.
Keywords: Travel -- Fiction; Drugs -- Fiction